Вплив фінансової незалежності жінки на сексуальні взаємини - Федоренко, Раїса Петрівна; Fedorenko, Raisa P. (Рівненський державний гуманітарний університет, 2014)
У статті запропоновано теоретичний огляд соціальних факторів, що спричинили прагнення жінки до фінансової незалежності; розкрито особливості сексуальних взаємин партнерів та вплив на них фінансової незалежності жінки.

This article shows the results of the theoretical research and empirical consideration of woman’s financial self-sufficiency influence on sexual relations within a couple; social factors that caused woman’s financial self-sufficiency and independence drive with or without a partner were characterized. It is established that a masculine and an androgynous type predominates among the women, who call themselves financially self-sufficient. It was defined, that the leadership qualities expression but not the financial self-sufficiency influences sexual relations. The analysis of the processed data revealed, that the brighter the leadership qualities are the more confident in their actions and decisions the respondents are. Along with it, the need gratification always dominates upon the partner’s desires. An androgynous and, partly, masculine type of the women belong to this class. A feminine woman, whose low rate of leadership qualities predominates, tend to gratify their partner’s need, and may also yield to their partner’s desires.
An influence of woman's financial self-sufficiency on the sexual relations
Keywords: психічні травми; маскулінність; фемінність; андрогінність; фінансова незалежність; лідерські якості; інститут сім’ї; psychic traumas; masculinity; femininity; androgyny; financial self-sufficiency; leadership qualities; family institution